Effectiveness and safety of capecitabine with or without bevacizumab as maintenance therapy in metastatic colorectal cancer: Real-world evidence from Vietnam - Cuc, Hoang Thi; Thang, Tran; Que, Pham Thi; Tan, Hoang Ngoc; Anh, Nguyen Thi Kim; Sach, Tran Viet; Phuong, Pham Thanh; Huy, Nguyen Van; Thinh, Tran Huy (Tạp chí Nghiên cứu Y học, 2026)
This retrospective cohort study evaluated the effectiveness and safety of capecitabine-based maintenance therapy in 182 Vietnamese patients with recurrent or metastatic colorectal cancer who achieved disease control after first-line CAPOX plus bevacizumab. Among them, 114 received bevacizumab-capecitabine and 68 received capecitabine alone. Median progression-free survival and overall survival for the whole cohort were 7.9 and 29.6 months, respectively. Compared with capecitabine monotherapy, bevacizumab-capecitabine maintenance was associated with significantly longer progression-free survival (11.2 vs. 5.5 months) and overall survival (36.5 vs. 23.5 months). In multivariable analysis, capecitabine monotherapy was independently associated with a higher risk of progression and death, while response to first-line treatment predicted longer progression-free survival and a higher number of metastatic sites was associated with worse overall survival. Both regimens were generally well tolerated, with most adverse events being grade 1-2 and no treatment-related death. These findings suggest that bevacizumab plus capecitabine is an effective and tolerable maintenance strategy for appropriately selected patients with metastatic colorectal cancer in routine Vietnamese clinical practice.